Damage Induced by Neutron Radiation on Output Characteristics of Solar Cells, Photodiodes, and Phototransistors - Biljana Simić; Dejan Nikolić; Koviljka Stanković; Ljubinko Timotijević; Srboljub Stanković (International Journal of Photoenergy)
This study investigates the effects of neutron radiation on I-V characteristics (current dependance on voltage) of commercial optoelectronic devices (silicon photodiodes, phototransistors, and solar panels). Current-voltage characteristics of the samples were measured at room temperature before and after irradiation. The diodes were irradiated using Am-Be neutron source with neutron emission of 2.7×106 n/s. The results showed a decrease in photocurrent for all samples which could be due to the existence of neutron-induced displacement defects introduced into the semiconductor lattice. The process of annealing has also been observed. A comparative analysis of measurement results has been performed in order to determine the reliability of optoelectronic devices in radiation environments.